PENGARUH KUALITAS AUDIT, KINERJA KEUANGAN, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dwi Yanti (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to examine the influence of quality audit, financial perform, and firm size towards good corporate governance disclosurein company. The population in this study are companies LQ45 listed in Indonesia Stock Exchange 2011-2013. The technique of sampling uses non-random sampling method with purposive sampling method was obtained 21 companies which were the sample of the observations carried on as much as three years. The hypothesis has been tested by using multiple regression method with the SPSS version 17.0. The results show that the first hypothesis (H1) states quality audit affect good corporate governance disclosure, rejected. The second hypothesis (H2) states financial perform affect good corporate governance disclosure, rejected. The third hypothesis (H3) states firm size affect good corporate governance disclosure, accepted.